2022
DOI: 10.1101/2022.03.21.485166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of the MICOS complex leads to an aberrant cristae structure and an unexpected, pronounced lifespan extension in Podospora anserina

Abstract: Mitochondria are dynamic eukaryotic organelles involved in a variety of essential cellular processes including the generation of adenosine triphosphate (ATP) and reactive oxygen species (ROS) as well as in the control of apoptosis and autophagy. Impairments of mitochondrial functions lead to aging and disease. Previous works with the ascomycete Podospora anserina demonstrated that mitochondrial morphotype as well as mitochondrial ultrastructure change during aging. The latter goes along with an age-dependent r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 97 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…In contrast to ∆PaTaz1, the ∆PaMic26/ ∆PaTaz1 double mutant still had an extended lifespan (Figure 3E,F), despite the lack of longchained CL species. Based on our previously described data, we concluded that longevity of the Mic10-subcomplex mutant ∆PaMic26 is the result of ROS-dependent mitohormesis [21] and does not depend on phospholipid metabolism. This conclusion is supported by the finding that loss of long-chained CL species in the mutant background only partially abrogates lifespan extension.…”
Section: Ablation Of Pataz1 Dramatically Impacts Phospholipid Metabolismmentioning
confidence: 57%
See 3 more Smart Citations
“…In contrast to ∆PaTaz1, the ∆PaMic26/ ∆PaTaz1 double mutant still had an extended lifespan (Figure 3E,F), despite the lack of longchained CL species. Based on our previously described data, we concluded that longevity of the Mic10-subcomplex mutant ∆PaMic26 is the result of ROS-dependent mitohormesis [21] and does not depend on phospholipid metabolism. This conclusion is supported by the finding that loss of long-chained CL species in the mutant background only partially abrogates lifespan extension.…”
Section: Ablation Of Pataz1 Dramatically Impacts Phospholipid Metabolismmentioning
confidence: 57%
“…We found that loss of each of the two MICOS subcomplexes leads to unexpected longevity. While loss of Mic10-subcomplex results in mitohormesis-induced lifespan extension, the underlying mechanism leading to longevity in Mic60-subcomplex mutants appears to be caused by a different mechanism which may be linked to phospholipid metabolism [21]. This possibility is supported by the demonstration of the interaction between human MIC60 and components of the cardiolipin synthesis pathway, including phosphatidylglycerophosphate synthase (PGS1) and cardiolipin synthase (CRD1) [22].…”
Section: Loss Of Micos Subunits Leads To Changes In Phospholipid Meta...mentioning
confidence: 99%
See 2 more Smart Citations
“…ICMs are often continuous with, but sometimes detached from 46 , the cytoplasmic membrane (CM) 47 , just as cristae are continuous with the mitochondrial inner membrane. In S. cerevisiae mitochondria, the disruption of Mic60 leads to functional defects such as decreased growth rate under respiratory conditions (i.e., non-fermentable media) and increased production of oxygen radicals 48,49 . If Mic60 is involved in the development of photosynthetic ICMs, then its disruption should lead to growth defects in the absence of oxygen and the presence of light (i.e., photosynthetic conditions).…”
Section: Resultsmentioning
confidence: 99%